Die Benutzung Story Box der Medien Im Schreibfertigkeit Auf Deutsch In Der Klasse XI A1 An Der SMAN 1 Lumajang - RAHMA OKTRINDA, ELINNA (LATERNE, 2014)
The use of media in teaching is how to distribute learning materials that can stimulate attention, interests, thoughts, and feelings of students in learning activities to achieve specific learning goals. Story Boxes utilizing media support to help students to improve students' writing abilities. Story boxes or story box is a container used to store or save media to enhance reading and increase the variety of different activities to promote the language and its use. Writing skills categorized into skills that are productive and complex. Students as learners in demand can be ideas, thoughts and opinions themselves with proper language and good, especially in foreign language learning, especially learning German language learners in demand to master the elements of language such as vocabulary, spelling, word order in sentences, and Grammatik. Henry Thunder Tarin (1986: 15), describes the definition of writing as activity ideas / ideas using written language as a medium conveys, while Jung (1992: 12) also says that "Schreiben ist ein h?chst komplexe Fertigkeit, die eine und gedakliche sprachliche Tätigkeit bei Kenntnis im Bereich des gleichzeitigen Wortschatzes, Grammatik der, der Text konstuktion Bereich und jewelligen thematischen verlangt. The focus of this research is the problem in the use of media in teaching writing skills. The question in this study is specific to the skills learning how to write the story the media boxes A1 class XI of SMAN 1 Lumajang? While the purpose of this study is to describe the learning process of writing skills by using the media story boxes A1 class XI of SMAN 1 Lumajang. The discussion in this study using a quantitative research model to describe the process of learning the writing skills of students in class XI students of SMAN 1 Lumajang A1. The steps for using media story boxes are as follows: 1. Orientation 2. Presentation 3. Structured Exercise 4. Guided Exercise 5. Exercise independent. From the results of the first phase of research that can run well, students were excited. In the second stage can work well as expected, because at the time of the presentation students were enthusiastic about the medium used. In the third phase can work well, but it appears there are some students who are still difficulties in formulating a sentence. In the fourth stage can run well students can socialize well in groups, but there are still obstacles at the beginning of the formation of student groups that are less conducive classroom atmosphere becomes less controllable. In the fifth stage can run well, students work on questions given by the teacher well, but still found some errors in the preparation of the student sentences. From the results of research conducted learning writing skills class XI A1 SMAN 1 Lumajang use media story box can run well and make students more active and motivated to learn. Addition of supporting data used in this study, the value of the post-test students has increased compared to pre-test values. keyword : The use of the media story box, writing skills